Analysis Of Added Value Of Turmeric Biopharmaceutical AgroindustryIn Ponorogo District - Hidayatun Nufus; Gusti Randy Pratama; Devi Urianty Miftahul R (Agroindustrial Technology Journal, 2021)
Ponorogo regency has the potential to increase the yield of natural resources such as biopharmaceutical plant types. One type of biopharmaceutical plant in Ponorogo Regency is a turmeric plant produced in 14 sub-districts. This research aims to: a) Identify the flow of agroindustry value chain distribution of turmeric commodity biopharmaceuticals by mapping BPMN (business process model and notation). b) Calculate the added value of Agroindustri biopharmaceutical turmeric commodity with hayami analysis. In this study, there are two conclusions. First, mapping using BPMN (Business Process Model and Notation): The distribution pattern of turmeric commodities in Ponorogo Regency there are two distribution patterns that run through crates, collectors and local distributors and exporters. Second, added value based on the hayami method, obtained the result of the comparison of added value farmers: Steamers: local distributors are 9%: 55% : 36%. While the added value of the flow of exporters is farmers 8.5%: steamers52.7% : exporters 38.8%